Pemodelan Sistem Terintegrasi Lembaga Sertifikasi Profesi Politeknik Negeri Manado Untuk Pengembangan WEB Dengan Metode Rapid Application Development (RAD) - Diane Tangian; Edwin Lumunon; Dimas Ero Permana (Prosiding Seminar Nasional Produk Terapan Unggulan Vokasi, 2022)
Manado State Polytechnic’s LSP (Institution of Professional Certification ) is an institution within Manado State Polytechnic that runs its function to do competence tests at each TUK (Competence Test Place) according to MUK (Competence Test Material). Students who are at their last semester will be tests their competence based on their field of study. Sometimes the tests are conduct online which leads to the need of website system that contain MUK. The system shoould also cope with scoring of the students and their pass or not pass status. These data will be reported to BNSP (National Institution of Professional Certification). So, website and its application is a need to cope with competence test processes, from TUK data, MUK materials, up until recapitulation of students that has K or BK status, which will be reported to BNSP. During website development, it needs a well organized system modelling. The modeling is planned to be fast as the system is in urgent. Since the system is not a large one, the development could be done using Rapid Application Development (RAD). The system will be used in logical design as well as physical design, to become a full functional and responsive system.